Uso de geotecnologias para identificação de ilícitos: plantio de coca na fronteira amazônica Peru-Brasil - Oliveira, Sandro Sales De (2018)
The main goal of this work is to study the relationship between deforestation caused by man and the recent coca planting activity in the inter - fluvial region between the Amazon River and the Javari River, on the border of Brazil and Peru. For this, it was necessary to find geographically the areas most affected by deforestation, within the border region, between the Javari and Amazon Rivers, in the region called Bajo Amazonas in Peruvian territory, called Trapézio Amazônico. It was also necessary to calculate the deforestation rates observed in the Amazon Trapezoid area and later, it was necessary to analyze the dynamics of these deforestation, as well as to show the possible determinants of this anthropization. The methodology adopted took into account a series of indications that coca plantations in the region had as their objective the production of cocaine base paste for the purpose of entering the Brazilian territory. The data of UNODC and a set of satellite images (LANDSAT) were used as source of primary data where the anthropic areas were observed in the studied region. The materials used consisted of various information produced by the police operations that occurred in the region, official information from the Peruvian government and a series of documentaries and reports obtained from open sources on the Internet. The method for obtaining the deforestation polygons consisted in the definition of the geographical area, selection and acquisition of satellite images, definition of the studied period and the digital processing of the images so that at the end of the process the polygons of deforestation were extracted from the years of 1992, 2000, 2006, 2011 and 2015. It was attempted to contextualize the issue of drug trafficking, territoriality and the use of geotechnologies as a tool for analyzing criminal data in independent chapters highlighting the use of geotechnologies to identify illicit; the characterization of the defined area of coca planting in the studied region; the historical formation of the northwest border and the issue of coca and cocaine. The results presented pointed out the quantitative of the anthropic areas accumulated in the years 1992, 2000, 2006, 2011 and 2015. During this period there was a growth of around 600% of deforestation in the region under study. Between 2006 and 2011, the largest increase (86%) was observed, which according to the official documents and interviews with institutional actors involved in operations to combat international drug trafficking, was also evident in the period in which the crops and drug trafficking in the Amazon region. Finally, it was possible to identify geographically that the areas most affected by deforestation in the Lower Amazon region in Peruvian territory were also those where official information indicated an increase in coca plantations. These statements were reinforced by the statements of the main institutional actors involved in the police operations carried out in that region.